Penerapan Pembelajaran Inovatif STEAM di Sekolah Dasar - Ana Nurhasanah; Zelela MS (JIKAP PGSD: Jurnal Ilmiah Ilmu Kependidikan, 2021)
This study aims to describe the application of innovative STEAM learning in primary schools in the city of Serang. This research was conducted using a narrative method with interview techniques. The subjects of this study were fifth-grade teachers at SDN 1 Pamarican, Serang City, Banten. Data were collected through interviews and documentation. The results showed that the application of innovative STEAM learning was as follows: 1) STEAM learning planning which was developed in guiding educators to carry out their duties as educators in serving the learning activities of their students; 2) Learning planning is seen as a tool that can help educators be more efficient in carrying out their duties and functions more effectively, on time, and provide opportunities for easier control and monitoring of their implementation; 3) each topic discussed must be appropriate in relation to components including science, technology, engineering, art and mathematics; and 4) the assessment must be in accordance with the performance objectives that have been set. Thus students through STEAM's innovative learning have direct experience so that they build a more meaningful understanding of learning materials. Educators become facilitators who facilitate learning by organizing teaching materials, delivering strategies, and managing activities by taking into account the objectives, obstacles, and characteristics of students so that effective and efficient results are obtained.